0/2 h-Algorithm for Rapid Triage of Suspected Myocardial Infarction Using a Novel High-Sensitivity Cardiac Troponin I Assay. (25th November 2021) - Wildi, Karin; Boeddinghaus, Jasper; Nestelberger, Thomas; Lopez-Ayala, Pedro; Yufera Sanchez, Ana; Okamura, Bernhard; Shrestha, Samyut; Rohner, Jennifer; Miró, Òscar; Martinez-Nadal, Gemma; Martin-Sanchez, F Javier; Koechlin, Luca; et al.
Abstract: Background: We aimed to derive and validate a 0/2 h-algorithm using the new high-sensitivity cardiac troponin I (hs-cTnI)-VITROS assay (VITROS ® Immunodiagnostic Products hs-Troponin I Reagent Pack, Ortho Clinical Diagnostics) for rapid rule-out/in of non-ST-segment elevation myocardial infarction (NSTEMI). Methods: The final diagnosis was centrally adjudicated by 2 independent cardiologists according to the fourth universal definition of myocardial infarction (MI) among 1888 patients presenting to the emergency department with acute chest pain. hs-cTnI-VITROS concentrations were measured at presentation and at 2 h in a blinded fashion. The optimal assay-specific thresholds for the hs-cTnI-VITROS 0/2 h-algorithm were derived in a randomly selected 70% of the cohort and validated in the remaining 30%. Results: NSTEMI was the final diagnosis in 216/1322 (16.3%) patients of the derivation cohort. Rule-out was defined as baseline hs-cTnI concentrations of <1 ng/L in patients presenting with chest pain onset >3 h or a baseline hs-cTnI concentration of <2 ng/L and an absolute change of <3 ng/L within 2 h. Thresholds for rule-in were either ≥40 ng/L at presentation or an absolute change within 2 h of ≥ 5ng/L. In the derivation cohort, these thresholds ruled-out 50.8% of patients with a negative predictive value (NPV) and sensitivity of 99.7% (95% Confidence Interval (CI), 98.8–99.9%) and 99.1% (95% CI, 96.7–99.9%), and ruled-in 17.9% with a positive predictive value (PPV) of 79.2% (95% CI, 74.3–83.5%). In the validation cohort, NSTEMI was the final diagnosis in 91/566 (16.1%) patients. The derived 0/2 h-algorithm ruled-out 46.3% of patients with a NPV and sensitivity of 100% (95% CI, 95.6–100%) and 100% (95% CI, 96.0–100%), and ruled-in 18.9% with a PPV of 73.8% (95% CI, 66.1–80.3%) in the validation cohort. Conclusion: hs-cTnI-VITROS concentrations at presentation combined with absolute changes within the first 2 h allowed safe rule-out and accurate rule-in of NSTEMI in two-thirds of unselected patients presenting with acute chest pain to the emergency department. Trial registration: www.clinicaltrials.gov : NCT0047058